Review of Hydraulic Equipment Maintance Strategy to Reduce Oil Consumption Cost in Hot Strip Mill PT KS - Suwarto, Agus; Yudoko, Gatot (The Indonesian Journal of Business Administration, 2013)
Currently, every company should do efficiency to reduce the production cost in order to increase it product competitiveness in both local and international market. Maintenance activity cost is the one of management concern to reduce without sacrificing the reliability of equipment and machine performance. The average lubricant usage cost in Hot Strip Mill PT. KS is Rp 1.149.464.558,- per-month or total Rp 13.793.574.699,- for year 2011, and this is a serious problem because it tends to increase every year. There are many kinds of lubricants (oil and grease) which are used in Hot Strip Mill PT. Krakatau Steel as bearing lubrication system, gear lubrication system and as fluid media in hydraulic system to move the equipment with heavy load. To reduce the lubricant cost is by doing identification of hydraulic equipment which is using the biggest of oil consumption cost for Rp 3.287.476.000,- per-year. Because there are some hydraulic system in Hot Strip Mill, therefore the research is focusing on hydraulic system in Finishing Mill area which is the biggest contributor on oil consumption by 825.691.647,- per-year.The main cause of high oil consumption cost is leakage on hydraulic hose and hydraulic cylinder seal because there is no periodically replacement schedule. Therefore, it is suggested to implement the maintenance strategy both for preventive and predictive maintenance strategy based on equipment criticality factor or impact will occur when equipment failure such as: workforce safety, production downtime, product quality, equipment duty of operation and the inspection possibilities during equipment running. By implementing an appropriate maintenance strategy, the company will get cost saving Rp 87.838.138,- per-year or 10,6 % from oil consumption cost.Â Keywords: lubricant usage cost, preventive and predictive maintenance strategy, increase company competitiveness.